Inhibition of ferroptosis protects House Ear Institute‐Organ of Corti 1 cells and cochlear hair cells from cisplatin‐induced ototoxicity. Issue 20 (14th September 2020) - Mei, Honglin; Zhao, Liping; Li, Wen; Zheng, Zhiwei; Tang, Dongmei; Lu, Xiaoling; He, Yingzi
Abstract: Ferroptosis is a recently recognized form of non‐apoptotic cell death caused by an iron‐dependent accumulation of lipid hydroperoxides, which plays important roles in a wide spectrum of pathological conditions. The present study was aimed to investigate the impact of ferroptosis on cisplatin‐induced sensory hair cell damage. Cell viability was determined by Cell Counting Kit‐8 and lactase dehydrogenase assays. The reactive oxygen species (ROS) levels were evaluated by 2, 7‐Dichlorodi‐hydrofluorescein diacetate (DCFH‐DA) and MitoSox‐Red staining. Mitochondrial membrane potential (MMP) was measured by tetramethylrhodamine methyl ester (TMRM) staining. Lipid peroxidation,  intracellular and mitochondrial iron were detected by Liperfluo, C11‐BODIPY 581/591, FerroOrange and Mito‐FerroGreen, respectively. We found that cisplatin treatment not only markedly augmented ROS accumulation, decreased the MMP, but increased lipid peroxidation and iron accumulation in House Ear Institute‐Organ of Corti 1 (HEI‐OC1) cells. Of note, treatment with the specific ferroptosis inhibitor ferrostatin‐1 could effectively abrogate the cisplatin‐induced toxicity and subsequent cell death. Specifically, the improvement of mitochondrial functions is important mechanisms for protective action of ferroptosis inhibitor against cisplatin‐induced damages in HEI‐OC1 cells. Moreover, inhibition of ferroptosis significantly protected murine cochlear hair cells against cisplatin damage. In addition, treatment murine cochlear hair cells with ferroptosis inducer, RSL3, significantly exacerbated cisplatin‐induced damage, which could be alleviated by ROS inhibitor N‐acetyl‐L‐cysteine. Collectively, our study indicated that ferroptosis inhibition could alleviate the cisplatin‐induced ototoxicity via inactivation of lipid peroxide radical and improvement of mitochondrial function in hair cells.